2017
DOI: 10.1080/15570274.2017.1354458
|View full text |Cite
|
Sign up to set email alerts
|

Combating the Cult of ISIS: A Social Approach to Countering Violent Extremism

Abstract: the review of faith & international affairs | 14 programs (Wagner 2015). These student-led programs create social media and web-based platforms designed to refute and combat ideology-based radicalization. The State Department also coordinates a global engagement campaign called "Think again. Turn away." This campaign, centered around a presence on Twitter, acts as a US-funded "myth-buster," seeking out disparaging evidence that contradicts the lure of ISIS (DOS 2017). These sorts of rhetorically based programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Sektarisme kan zodoende net als extremisme als een subcategorie van radicalisme worden beschouwd, gezien de non-conformistische aard van beide type ideologieën. Bovendien kunnen extremistische groeperingen zoals IS volgens sommigen eveneens als 'sekte' worden aangeduid door hun gesloten karakter (zie bijvoorbeeld Day & Kleinmann, 2017;Stein, 2021) -wat de onderlinge verbanden tussen deze ideologieën verder onderstreept. Het is deze gedeelde fundamentele antipathie tegen de heersende maatschappelijke en/of politieke orde die de overdracht van extreme ideologieën als onderzoeksobject onderscheidt van 'reguliere' overdachtsprocessen.…”
Section: De Overdracht Van Extreme Ideologieënunclassified
“…Sektarisme kan zodoende net als extremisme als een subcategorie van radicalisme worden beschouwd, gezien de non-conformistische aard van beide type ideologieën. Bovendien kunnen extremistische groeperingen zoals IS volgens sommigen eveneens als 'sekte' worden aangeduid door hun gesloten karakter (zie bijvoorbeeld Day & Kleinmann, 2017;Stein, 2021) -wat de onderlinge verbanden tussen deze ideologieën verder onderstreept. Het is deze gedeelde fundamentele antipathie tegen de heersende maatschappelijke en/of politieke orde die de overdracht van extreme ideologieën als onderzoeksobject onderscheidt van 'reguliere' overdachtsprocessen.…”
Section: De Overdracht Van Extreme Ideologieënunclassified
“…This nexus between social capital and resilience nexus is responsive to an understanding of violent extremism itself as a complex, dynamic, multisited ideological, and behavioral matrix in which multilevel and multisystemic influences, networks, capacities, resources, and vulnerabilities converge to enable a distinctive form of violent social and political threat or attack. If the drivers and attractors of violent extremism are bound up with social conditions, protections, dynamics, and adversities, in whatever proportion, then so too must be the solutions that seek to prevent, divert, or rechannel these factors (Day & Kleinmann, 2017). Community resilience paradigms thus offer a socially attractive, policy-, and investmentfriendly way forward in relation to conceptualizing what an integrated multisystemic social and political response might look like, one that draws individuals, communities, governments, and sometimes the private sector together in new collaborative relationships and partnerships.…”
Section: The Importance Of Social Capital To P/ Cve Resilience Modelsmentioning
confidence: 99%
“…29 In their study of counter-extremism programs (CVE), Day and Kleimann have similarly shown that exposure to counter-narratives tends to produce a psychological "backfire effect" and pushes individuals toward further radicalization. 30 The more individuals value a particular identity, the more committed they will consequently be to reaffirm it when confronted to perceived threats to their self-concept.…”
Section: Research Approach and Theoretical Frameworkmentioning
confidence: 99%